2012
DOI: 10.1186/2047-783x-17-14
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of hyperbaric oxygen and iloprost on ischemia/reperfusion-induced lung injury in a rabbit model

Abstract: BackgroundThe role of multiorgan damage in the mortality caused by ischemic limb injury is still not clarified. The objective of this study was to examine the potential protective effects of hyperbaric oxygen (HBO) and iloprost (IL) therapy on lung damage induced by limb ischemia/reperfusion injury in a rabbit model, using both biochemical and histopathological aspects.MethodsForty New Zealand white rabbits were randomly allocated into one of five study groups: HBO group (single session of HBO treatment); IL g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…The experimental procedure for I/R-induced ALI was conducted according to published protocols with minor modifications 39-41 . Rats were randomized into sham-operated, and lung I/R groups with or without rhMG53 treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure for I/R-induced ALI was conducted according to published protocols with minor modifications 39-41 . Rats were randomized into sham-operated, and lung I/R groups with or without rhMG53 treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive production of ROS causes lipid peroxidation in cell membranes and oxidative damage to DNA and proteins (16). A number of agents, such as N-acetylcystein, calcium dobesilate, aprotinin, erdosteine or magnesium sulfate have been proposed to be useful against lung injury induced by I/R (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…al., [5] studies showed that HBO and IL reduces lipid peroxidation minimizing the injury after reperfusion. The combined therapy is shown to be more effective than either treatment given alone.…”
Section: Hyperbaric Oxygen (Hbo) and Iloprost (Il) Therapymentioning
confidence: 99%
“…The aim of the present review is to display the role of those treatments and their level of success, reporting the effective ones in reducing the extension of the injury caused by reperfusion and its aspects [1,2,3,5,6,7,8,11,12,13,15,16,17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation